2016
DOI: 10.1902/jop.2015.150345
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Conditions in Human Immunodeficiency Virus–Positive Patients Under Highly Active Antiretroviral Therapy From a Metropolitan Area of Rio De Janeiro

Abstract: The current investigation demonstrates that HIV+ individuals under HAART presents a high prevalence of mild to moderate periodontal disease. Viral load levels, CD4+ nadir, and CD4+ counts may present a weak to moderate correlation to the number of missing teeth, periodontal diagnosis, moderate PD, and moderate CAL, which may also reflect some effect of these systemic conditions on the periodontal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Smoke components may impair the innate immune system against pathogens, alter antigen presentation and modulate the adaptive immune response 44,45 . In other studies periodontitis was also more prevalent in smoking compared to non-smoking HIV-infected patients 16,19 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Smoke components may impair the innate immune system against pathogens, alter antigen presentation and modulate the adaptive immune response 44,45 . In other studies periodontitis was also more prevalent in smoking compared to non-smoking HIV-infected patients 16,19 .…”
Section: Discussionmentioning
confidence: 65%
“…After the introduction of cART, the reported prevalence of periodontitis in HIV infected patients varied even more widely. For instance, in a study in India among 130 HIV infected patients, a prevalence of periodontitis of 20% was found 15 while a very small study (n=29) in Brazil reported a prevalence of 86% 16 . This variation can be explained by the different definitions used in the studies 17,18 , differences in social and economic status 19 as well as the availability of dental care and oral care awareness and the attitudes of dental practitioners 20 .…”
Section: Introductionmentioning
confidence: 98%
“…Oral lesions are one of the most important indicators of HIV infection 4 , 5 , 6 , 7 . The presence of oral lesions in HIV+ patients is correlated with high viral load and low CD4+ cell counts 8 , 9 . Some studies have reported differences in the prevalence of oral manifestations associated with HIV infection 5 , 7 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%